Pengaruh Ketersediaan, Efektivitas dan Kemudahan Penggunaan Qris terhadap Keputusan Pembelian serta Dampaknya Bagi Karakter Generasi Muda - Nurdiana FI; Imam Baidlowi; Yuliasnita Verlandes; Agoes Hadi Purnomo; Adhe Sarah (Jurnal Ekonomi Manajemen Akuntansi, 2024)
The new era of digitalization created by humans has touched various aspects including transaction payment methods. With digital payments, humans make payments with just one scan. Bank Indonesia, in collaboration with ASPI, launched digital payment Qris in 2020. Qris was initially a payment solution during the pandemic that was accepted by the public and is still widely used today. Including the younger generation, they often use Qris to make payments. This research aims to identify the influence of the availability, effectiveness and ease of use of Qris on purchasing decisions and its impact on the character of the younger generation. Using the quantitative SAM PLS method and qualitative literature study, the research took samples of student members of the GMNI organization who met the criteria. The results of data processing showed that the variables of availability, effectiveness and ease of use of Qris had a positive and significant effect on purchasing decisions. The impact of using Qris for the younger generation is a shift in disciplined, independent and responsible character due to the ease of payment facilities which gives rise to consumer behavior. This can be handled with supervision and character education starting at the family, school, community and government levels. By synergizing together, a strong character can be built in the younger generation, able to answer problems and be of benefit to the wider community.